2018
DOI: 10.1111/ppl.12732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium and its interaction with phosphorus on the nutrient status and growth of three Lupinus species

Abstract: Phosphorus (P)-deficiency symptoms are known for Lupinus species grown in calcareous soil, but we do not know if this is due to a high calcium (Ca) availability or a low P availability in the soil. To address this problem, we explored both the effects of Ca and its interactions with P on nutrient status and growth of three Lupinus species. Two Ca-sensitive genotypes (L. angustifolius L. P26723 and L. cosentinii Guss. P27225) and two Ca-tolerant genotypes (L. angustifolius L. cv Mandelup and L. pilosus Murr. P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
(83 reference statements)
1
3
0
Order By: Relevance
“…In addition, the shoot and total biomass of L. pilosus under a high Ca supply was actually significantly greater than that of control plants. This confirms our finding that Ca improves the shoot growth of species that grow well under an extremely high Ca concentration (Ding et al 2018a). The negative effects of high pH and/or high pH + high Ca on total root length of Lupinus species agree with the decreased lateral root growth of some Lupinus species grown in either a high pH (buffered by MES/TES or caused by high [HCO3 -]) nutrient solution (Ding et al, personal observations) or limed soil .…”
Section: Plant Growthsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the shoot and total biomass of L. pilosus under a high Ca supply was actually significantly greater than that of control plants. This confirms our finding that Ca improves the shoot growth of species that grow well under an extremely high Ca concentration (Ding et al 2018a). The negative effects of high pH and/or high pH + high Ca on total root length of Lupinus species agree with the decreased lateral root growth of some Lupinus species grown in either a high pH (buffered by MES/TES or caused by high [HCO3 -]) nutrient solution (Ding et al, personal observations) or limed soil .…”
Section: Plant Growthsupporting
confidence: 92%
“…Excessive Ca may precipitate with P as Ca3(PO4)2 in plant tissues which makes both Ca and P unavailable (Ding et al 2018b;McLaughlin and Wimmer 1999;Zohlen and Tyler 2004). We found that Ca-tolerant Lupinus species tended to have tight control over Ca uptake and/or translocation from roots to leaves, or better Ca compartmentation at the cellular level (Ding et al 2018a). These abilities likely play an important role in the tolerance of some Lupinus species to calcareous soils, as suggested for other calcicole species (He et al 2014;Jefferies and Willis 1964;Raza et al 2000;Valentinuzzi et al 2015;Webb 1999;Wu et al 2011).…”
Section: Introductionmentioning
confidence: 92%
“…However, due to high user risks, liquid propane becomes practically and operationally unfeasible. Areas of freezing damage evident in our samples are much smaller in scale than our regions of analysis, and in many cases, little-to-no damage is seen in plant samples frozen in liquid N at this scale (Ding et al, 2018;Guilherme Pereira et al, 2018;Hayes et al, 2019;Kotula et al, 2019;Ding et al, 2020). With this, we maintain that imaging and analysis of samples in their frozen state offers the best prospect of preserving cellular integrity, compared to chemical and resin-based preparations, which have the potential to extract components (e.g., lipids), create distortions (e.g., following dehydration), and result in the dissolution of ions (e.g., loss or movement of soluble ions and compounds).…”
Section: Cryosem To Evaluate Symbiosismentioning
confidence: 78%
“…First, the cellular [P] in the mesophyll was probably too low to cause precipitation of Ca and P, due to the low soil P supply in the present study. Cellular [P] in the mesophyll is influenced by external P supply (Treeby et al, 1987;Ding et al, 2018b), with plants usually showing constitutive P-and Ca-allocation patterns at the species level (Guilherme Pereira et al, 2018). Thus, it would be interesting to explore whether and how chickpea sustains the co-existence of P and Ca in mesophyll cells at a higher soil P availability.…”
Section: Accepted Manuscriptmentioning
confidence: 99%